STRATEGIC MANAGEMENT OF THE INTER-RELIGIOUS HARMONY FORUM (FKUB) IN MAINTAINING INTER-RELIGIOUS HARMONY IN MEDAN CITY - Zein, Gilang Hardian; Simamora, Irma Yusriani (Pena Cendekia Insani, 2025)
Interfaith harmony is a major challenge in a multicultural society like Medan City, which has religious and cultural diversity. The Interfaith Harmony Forum (FKUB) is present as a non-structural institution that has a strategic role in maintaining social harmony through an inclusive da'wah approach, interfaith dialogue, and collaboration with the government and society. This study aims to determine the strategic management implemented by the Medan City FKUB in an effort to maintain interfaith harmony. This study uses a qualitative method with data collection techniques through observation and in-depth interviews with key figures in the FKUB. The results of the study indicate that the FKUB da'wah strategy focuses on a persuasive and dialogical approach, empowering religious figures as mediators, and utilizing social media as a means of digital da'wah. The challenges faced include misinterpretation of religious teachings, the negative influence of social media, and lack of participation of the younger generation. Therefore, this study recommends the implementation of an adaptive, participatory, and contextual da'wah approach to respond to contemporary socio-religious dynamics and strengthen interfaith harmony in Medan City.